Electrocatalytic oxygen reduction activity of AgCoCu oxides on reduced graphene oxide in alkaline media - Madakannu, Iyyappan; Patil, Indrajit; Kakade, Bhalchandra; Datta, Kasibhatta Kumara Ramanatha (Beilstein Journal of Nanotechnology, 2022)
Silver-based electrocatalysts as promising substitutes for platinum materials for cathodic oxygen electroreduction have been extensively researched. Electrocatalytic enhancement of the Ag nanoarchitectonics can be obtained via support structures and amalgamating Ag with one or two additional metals. The work presented here deals with a facile microwave-assisted synthesis to produce bimetallic Ag-Cu and Ag-Co (1:1) oxide nanoparticles (NPs) and trimetallic AgCuCo (0.6:1.5:1.5, 2:1:1, and 6:1:1) oxide NPs supported on a reduced graphene oxide (rGO) matrix. Morphology, composition, and functional groups were methodically analysed using various microscopic and spectroscopic techniques. The as-prepared electrocatalysts were employed as cathode substrates for the oxygen reduction reaction (ORR) in alkaline medium. Varying the Ag fraction in copper cobalt oxide has a significant influence on the ORR activity. At a ratio of 2:1:1, AgCuCo oxide NPs on rGO displayed the best values for onset potential, half-wave potential, and limiting current density (Jk) of 0.94 V vs RHE, 0.78 V, and 3.6 mA·cm−2, respectively, with an electrochemical active surface area of 66.92 m2·g−1 and a mass activity of 40.55 mA·mg−1. The optimum electrocatalyst shows considerable electrochemical stability over 10,000 cycles in 0.1 M KOH solution.
Keywords: copper cobalt oxide NPs; microwave synthesis; oxygen electroreduction; reduced graphene oxide; silver NPs